COMPARISON OF FOLEY’S CATHETER WITH EXTRA AMNIOTIC PROSTAGLANDIN F2 ALPHA IN TERMINATION OF SECOND TRIMESTER PREGNANCY - Nasreen, Abida; Akhtar, Shahnaz; Shaheen, Nighat (Journal of Postgraduate Medical Institute, 2011)
Aims and Objectives: The aim of this study was to compare the efficacy, safety, adverse effects and cost effectiveness of extra-amniotic Foley's catheter balloon alone (group-I), with the combined use of Foley's catheter balloon and extra-amniotic prostaglandin F2- Material and Methods: It was a experimental trial carried out in Obstetrics and Gynecology unit "A" of post-graduate medical institute, Lady Reading Hospital Peshawar, during September 2002 to September 2003. Results: Hundred (100) patients having gestational age between 14-28 weeks and cervical score less than 4, were enrolled in the study, 50 patients for group-I and 50 patients for group-II. Indications for termination were either intrauterine fetal death or congenital malformations incompatible with life. Foley's catheter 16fr was passed in both the groups intra-cervically. Group-II patients in addition received extra amniotic PGF2alpha, (0.25mg/ml diluted solution), one ml at one hour interval, through the same catheter, till the expulsion of the balloon. The mean induction to products expulsion interval was significantly shorter in the combined use of Foley's catheter and extra amniotic PGF2alpha (13.34±6.71 versus 33.74±8.941 hours). The rate of successful uterine expulsion with in 24 hrs was also significantly higher in group-11 (92% versus 24%). The frequency of diarrhea (04%), vomiting (06%), and uterine pain (06%) in group -11 was not statistically significant (P>0.05) but the frequency of temperature of 100 ºF was significantly higher in group-1 (78%) as compared to group-11(18%).Group-11 patients had shorter average hospital stay (1.53±0.57 days versus 2.766±0.567 ingroup-1 i.e. P<0.1). Conclusion: The combined use of Foley's catheter and extra amniotic PG F2 alpha is more rapid, safe, cost effective method for induction of therapeutic termination of second trimester pregnancy, resulting in greater number of successful uterine evacuation with in 24 hrs, than Foley's catheter balloon alone. á (group-II) for termination of second trimester pregnancy.